2004
DOI: 10.1074/jbc.m402144200
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Receptor Signaling Inhibits Glucocorticoid-induced Apoptosis by Repressing the SRG3 Expression via Ras Activation

Abstract: Activation of T cell antigen receptor (TCR) signaling inhibits glucocorticoid (GC)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 73 publications
1
36
0
Order By: Relevance
“…13,17,18 In this study, we have shown that Notch signaling directly repressed the E47-dependent SRG3 transcription (Figure 3). These results are consistent with previous reports that Notch and Deltex proteins abrogate E2A-induced transcriptional activation.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…13,17,18 In this study, we have shown that Notch signaling directly repressed the E47-dependent SRG3 transcription (Figure 3). These results are consistent with previous reports that Notch and Deltex proteins abrogate E2A-induced transcriptional activation.…”
Section: Discussionmentioning
confidence: 51%
“…11 We have previously shown that SRG3 plays a critical role in determining the GC sensitivity in thymocytes; its expression was downregulated in mature CD4 and CD8 cells, 13 and acts as a downstream target of TCR signaling in blocking the GC-induced apoptosis. 17,18 Here, we show that Notch signaling confers developing thymocytes GC resistance also by regulating the SRG3 expression through Deltex1 blocking the recruitment of p300 coactivator to E2A/HEB. It was suggested that Notch blocks GC-induced apoptosis through the RBP-J pathway of Notch signaling.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations